2013
DOI: 10.1371/journal.pone.0058056
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi’s Sarcoma-Associated Herpesvirus K3 and K5 Proteins Down Regulate Both DC-SIGN and DC-SIGNR

Abstract: Kaposi’s sarcoma-associated herpesvirus (KSHV) is the etiological agent of multicentric Castleman’s disease, primary effusion lymphoma and Kaposi’s sarcoma. In this study, we show that like the C-type lectin DC-SIGN, the closely related DC-SIGNR can also enhance KSHV infection. Following infection, they are both targeted for down modulation and our data indicate that the KSHV MARCH-family ubiquitin ligase K5 is mediating this regulation and subsequent targeting for degradation of DC-SIGN and DC-SIGNR in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 59 publications
(102 reference statements)
1
13
0
Order By: Relevance
“…The characterization of KSHV K3 and K5 deletion mutants confirmed the importance of K5 in surface receptor modulation, but surprisingly, no obvious changes in MHC-I surface expression were apparent in cells infected with K3-deficient viruses (47), indicating that K5, but not K3, plays a dominant role in the context of infected cells. Similar observations were made for KSHV-mediated downregulation of DC-SIGN and DC-SIGNR, two substrates that can be downregulated by either K3 or K5 (32).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…The characterization of KSHV K3 and K5 deletion mutants confirmed the importance of K5 in surface receptor modulation, but surprisingly, no obvious changes in MHC-I surface expression were apparent in cells infected with K3-deficient viruses (47), indicating that K5, but not K3, plays a dominant role in the context of infected cells. Similar observations were made for KSHV-mediated downregulation of DC-SIGN and DC-SIGNR, two substrates that can be downregulated by either K3 or K5 (32).…”
supporting
confidence: 76%
“…Subsequent studies revealed an increasing number of K5 substrates, including the NKT cell ligand CD1d (25); the MHC-Irelated molecule HFE (26); the adhesion molecules ICAM-1 (27,28), PECAM (29), VE-cadherin (30), ALCAM (31), DC-SIGN, and DC-SIGNR (32); the costimulatory molecule B7-2 (27,28); the NK cell-activating ligands, MICA, MICB, and AICL (33); the cellular restriction factor tetherin (34); the cytokine receptor interferon gamma receptor 1 (IFN-␥R1) (35); the plasma membrane t-SNARE syntaxin-4 (36); and the transforming growth factor ␤ (TGF-␤) family member BMPRII (37). In addition, Timms et al recently reported several novel K5 substrates, including 8 verified targets, CD32, CD33, CD99, EPHB4, Plexin A1, PMZL2, Kit (CD117), and IL9R (CD129), and 66 potential new targets, all of which were identified via a quantitative mass spectrometry approach (38).…”
mentioning
confidence: 99%
“…DC-SIGN-expressing HEK 293 (DC-HEK) cells, as reported by Lang et al (31) were grown in DMEM-F12 (Life Technologies, UK) containing 10% v/v FCS and blasticidin (5 µg/mL) (Gibco). The cells were grown on 13 mm glass cover slips till a monolayer of cells was formed and then incubated with 15 µg/mL of recombinant ghA, ghB, and ghC (MBP as a negative control) separately in serum free medium and left to incubate for 30 min in 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, KSHV K3 and K5 (also called modulator of the immune recognition (MIR) 1 and 2, respectively) are viral E3 ligases capable of ubiquitinating the MHC-I cytoplasmic tail to trigger internalization and proteasomal degradation of the MHC-I complex [ 205 , 242 , 243 ]. K3 and K5 proteins also have been shown to downregulate both C-type lectins, DC-SIGN, and DC-SIGNR by ubiquitin mediated degradation [ 206 ]. Similarly, KSHV K6, K4, and K4.1 encode three homologues of cellular chemokines: viral CC-chemokine ligand 1 vCCL1(vMIP1), vCCL2 (vMIP2), and vCCL3 (vMIP3), respectively [ 154 , 244 , 245 ].…”
Section: Lytic Proteins In Controlling Immune Regulation and Pathomentioning
confidence: 99%